Case Report: Fatal disseminated cytomegalovirus infection following cyclophosphamide therapy in a young patient with systemic lupus erythematosus - Jaber, Mohanad; Muhtasib, Loai; Qawasmeh, Hebatallah; Thalji, Mariam; Yaghmour, Hiba Y.; Hroob, Hasan; Al-Zughayyar, Ashraf; Dweik, Majed (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by autoantibody production and systemic inflammation. Immunosuppressive treatment is often required to achieve remission. While opportunistic infection rates have risen in this patient population, cytomegalovirus is one of the most lethal opportunistic infections with fatal consequences. Herein, we report a case of an 18-year-old female patient with a two-year history of SLE complicated by lupus nephritis who presented with gastrointestinal symptoms while on immunosuppressive medication. She then developed a cascade of serious complications, including colitis, fulminant liver failure, acute pancreatitis, and pneumonitis, which progressed to disseminated intravascular coagulation (DIC). Detailed investigations were conducted, and the patient was diagnosed with disseminated cytomegalovirus infection. Multidisciplinary supportive management failed to save her life. Disseminated CMV infection is a rare but deadly condition in patients with SLE. This case emphasizes the importance of maintaining a high level of suspicion and considering CMV infection as a differential diagnosis in patients with SLE on immunosuppressive therapy who have obvious gastrointestinal symptoms. This allows for early detection, timely management, and administration of antiviral drugs, leading to improved overall patient health outcomes.